EKSISTENSI A’RUPAMA SEBAGAI MEDIA PENDIDIKAN KARAKTER PADA SISWA SEKOLAH DASAR DALAM KAWASAN ADAT AMMATOA - Ahmad Fadhel; Muh. Arif Tarman; Ratnawati Ratnawati (Lembaga Pengembangan Kinerja Dosen, 2023)
Culture-based education has become a movement to raise public awareness to continue lifelong learning in overcoming all the changing and increasingly difficult challenges of life. In addition, education provides answers and solutions to the creation of culture based on the needs of the community in accordance with the values ​​and systems that apply in it. There are various cultures that can be used as educational media, one of which is a'rupama which is a character education medium for the younger generation, especially elementary school students in the Ammatoa customary area. The role of a'rupama as a medium for character education in the Ammatoa customary area which later became the background for this research. This study uses a mixed method research type, namely research that combines qualitative and quantitative research. This research was carried out in the Ammatoa customary area, the informants and samples in this study were the community and the younger generation, especially school students in the Ammatoa customary area. Data was collected through observation, in-depth interviews, literature study and questionnaires with a total sample of 56 of the 131 population. The data were then analyzed using spiral analysis. Based on the results of the analysis, it was found that a'rupama actually has a role as a medium of character education for the younger generation in the Ammatoa customary area in educating the younger generation through instilling positive values ​​that are considered to be able to shape the character of the younger generation to become a much better generation. The values ​​contained in A'rutama's stories are responsibility, hard work, honesty, communicative, creative, caring for the environment, discipline and curiosity. The presence of a'rupama can be an answer to the increase in educational media that can be used as a medium for character education in elementary schools. In its development, a'rupama experienced a number of obstacles which were feared to threaten the existence of a'rutama. community, indigenous peoples only focus on improving the family economy, a'rupama is not yet part of character education in elementary schools and technological development factors.